Singapore boreholes results with numerical and analytical simulation - Yap, Kai Xian (Nanyang Technological University, 2023)
This report addresses the escalating demand for efficient transportation tunnelling, particularly emphasizing the crucial need for rigorous testing and monitoring of tunnel liners. These liners are vital for ensuring their effectiveness under subterranean environments' varied and persistent stresses. Traditionally, concrete-based materials have been the standard for tunnel lining construction. However, considering Singapore's rapidly expanding Mass Rapid Transit (MRT) system and other underground infrastructure projects, there has been a growing interest in using Steel Fibre fibre-reinforced concrete (SFRC) liners, especially those with larger diameters. This innovative approach promises potential benefits in terms of strength and durability. Despite the promising attributes of SFRC, certain uncertainties and unexplored aspects exist regarding its application. This makes conducting a detailed comparative analysis of SFRC liners against traditional concrete liners imperative. Understanding their performance under real-world conditions is essential to validate the use of SFRC in future projects. To achieve this, the final year project outlined in this report will leverage advanced computer software to simulate various tunnel lining designs across different soil profiles specific to Singapore. This approach is intended to pinpoint and distinguish the key parameters that significantly impact liner behaviour. This proactive identification is crucial for guiding subsequent physical monitoring and testing phases. Employing computer software for extensive testing and analysis offers a more profound understanding of the potential application of SFRC linings in tunnel construction. The insights gained from these simulations are invaluable in identifying the potential limitations of current design methodologies employed by engineers and enhancing the accuracy of these methods. Presently, many design engineers rely on empirical formulas for tunnel lining designs. The simulation method, with its ability to provide more precise calculations, can revolutionize this aspect of design, particularly in selecting and utilizing materials for SFRC liners. This approach aims to ensure that SFRC liners are optimally designed for performance and exhibit superior durability. By harnessing the power of simulation, this project seeks to contribute significantly to the field of tunnel engineering, offering innovative solutions and paving the way for more resilient and efficient underground transportation networks. The ultimate goal is to ensure that these advanced liners meet the high demands of modern tunnel construction, aligning with Singapore's vision for a robust and future-ready underground infrastructure.